2016
DOI: 10.1186/s12889-016-3649-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the age at menarche on body composition in adulthood: results from two birth cohort studies

Abstract: BackgroundEvidence suggests that early menarche is positively associated with adiposity in adulthood. However, it is important to assess whether this association is due to early menarche or to the association of adiposity in late childhood with age at menarche. We evaluated the association between age at menarche and body composition in adolescence and adulthood, among subjects who have been prospectively followed in two Brazilian birth cohort studies.MethodsIn 1982 and 1993, the hospitals births in Pelotas we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 36 publications
1
39
0
3
Order By: Relevance
“…The reference group in all analyses comprised those with an age at menarche of 12 to 13 years. There is some variation across studies in the definition of early menarche (≤10, ≤11, or ≤12 years) and late menarche (≥14, ≥15, or ≥16 years), likely influenced by the size and information available in the specific study, but our categorization is in line with commonly used cutoff values 4, 5, 6, 7, 8, 10, 11, 14, 16…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reference group in all analyses comprised those with an age at menarche of 12 to 13 years. There is some variation across studies in the definition of early menarche (≤10, ≤11, or ≤12 years) and late menarche (≥14, ≥15, or ≥16 years), likely influenced by the size and information available in the specific study, but our categorization is in line with commonly used cutoff values 4, 5, 6, 7, 8, 10, 11, 14, 16…”
Section: Methodsmentioning
confidence: 99%
“…Early menarche is associated with reduced insulin sensitivity and higher glucose,1, 2, 3, 4, 5, 6, 7, 8, 9 higher triglycerides and cholesterol levels,2, 6, 10 higher blood pressure,4, 5, 11, 12 and greater waist circumference and body mass index (BMI) 4, 5, 13, 14, 15. In line with these findings, there is some but less consistent evidence of an association between age at menarche and cardiovascular disease (CVD) events 12, 16, 17, 18.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We leave the investigation on the relationship between month and season at birth and age at menarche, which was also studied in the context of the Northern hemisphere, to future research. On the other hand, compared with other studies that asked adult women to retrospectively recall their age at menarche, often many years later, we anticipate that recall bias for menarcheal age in our data should be relatively lower, given the relatively short time span between the occurrence of menarche and the interview date. Hence, we conclude that the age in years reported should be relatively reliable …”
Section: Discussionmentioning
confidence: 76%
“…2,5 Consistent with this literature, we found an association between prepubertal adiposity, for which BMI is a surrogate marker, and earlier menarche. 2,5,15,40,41 The literature has also highlighted the role of prepubertal skeletal maturity, in addition to adiposity, for menarcheal timing. 5,29,42 We proxied skeletal maturity with HAZ and found that HAZ at ß8 years had strong and independent predictive power, pointing to the importance of both HAZ and BMIZ for menarcheal timing.…”
Section: Discussionmentioning
confidence: 99%